The Role of Local Governments in Promoting the Creative Economy through Policies and Regulations - Adhi Susano; Meida Rachmawati (Edusight International Journal of Multidisciplinary Studies, 2026)
This research examines the role of regional governments in developing creative economy through targeted policy implementation and regulation. Creative economy has become a sector that contributes significantly to national economic growth with added value reaching IDR 1,211 trillion or 7.44% of GDP in 2019. The research employs qualitative methods with case study approach in five regions with progressive creative economy policies. Data was collected through in-depth interviews, observations, and policy document analysis. Results indicate regional government roles include regulatory, facilitative, and catalytic functions in creating conducive creative economy ecosystems. Key success factors include regional leadership commitment, adequate budget allocation, stakeholder synergy, and adaptation to local characteristics. This research provides strategic recommendations for regional governments to optimize creative economy potential through adaptive policies and innovation-supporting regulations.